Magnitude and determinants of obstetric case fatality rate among women with the direct causes of maternal deaths in Ethiopia: a national cross sectional study - Ayele Geleto; Catherine Chojenta; Tefera Taddele; Deborah Loxton (BMC, 2020)
Abstract Background In sub-Saharan Africa, maternal death due to direct obstetric complications remains an important health threat for women. A high direct obstetric case fatality rate indicates a poor quality of obstetric care. Therefore, this study was aimed at assessing the magnitude and determinants of the direct obstetric case fatality rate among women admitted to hospitals with direct maternal complications. Methods In 2015, the Ethiopian Public Health Institute conducted a national survey about emergency obstetric and newborn care in which data about maternal and neonatal health indicators were collected. Maternal health data from these large national dataset were analysed to address the objective of this study. Descriptive statistics were used to present hospital specific characteristics and the magnitude of direct obstetric case fatality rate. Logistic regression analysis was performed to examine determinants of the magnitude of direct obstetric case fatality rate and the degree of association was measured using an adjusted odds ratio with 95% confidence interval at p < 0.05. Results Overall, 335,054 deliveries were conducted at hospitals and 68,002 (20.3%) of these women experienced direct obstetric complications. Prolonged labour (23.4%) and hypertensive disorders (11.6%) were the two leading causes of obstetric complications. Among women who experienced direct obstetric complications, 435 died, resulting in the crude direct obstetric case fatality rate of 0.64% (95% CI: 0.58-0.70%). Hypertensive disorders (27.8%) and maternal haemorrhage (23.9%) were the two leading causes of maternal deaths. The direct obstetric case fatality rate varied considerably with the complications that occurred; highest in postpartum haemorrhage (2.88%) followed by ruptured uterus (2.71%). Considerable regional variations observed in the direct obstetric case fatality rate; ranged from 0.27% (95% CI: 0.20-0.37%) at Addis Ababa city to 3.82% (95% CI: 1.42-8.13%) at the Gambella region. Type of hospitals, managing authority and payment required for the service were significantly associated with the magnitude of direct obstetric case fatality rate. Conclusions The high direct obstetric case fatality rate is an indication for poor quality of obstetric care. Considerable regional differences occurred with regard to the direct obstetric case fatality rate. Interventions should focus on quality improvement initiatives and equitable resource distribution to tackle the regional disparities.